Edukasi Kesehatan Meningkatkan Pengetahuan Dan Keterampilan Keluarga Dalam Pencegahan Jatuh Pada Lansia - Nurhasanah, Aan; Nurdahlia, Nurdahlia (Poltekkes Kemenkes Jakarta III, 2020)
Health Education improves family knowledge and performance in preventing the risk of falling from Lania. The population is all the elderly in crocodile holes that have fallen. The number of samples is 50 people. Sampling with proportional sampling. Collected using a questionnaire and analyzed by univatriate, bivatriate (dependent t test), and multivatriate with manova analysis. The results of the study showed significant differences before and given health education on knowledge (p = 0.001) with a difference in the average value = 0.9183, and a family skills score with a value of p = 0.035) with a difference in the average value = 1,100. gender is assessed against the level of knowledge with a value of P value = 0,000 and the status of the job depends on the skill value of the p value of 0.001. then it can help the success of education can improve aspects of family knowledge and skills in making failures in the elderly. Provided that proper education is given to families as a form of self-care and to implement appropriate environmental management to prevent the risk of falls.